Implementasi Metode Indexing dan Penggunaan Subquery untuk Optimalisasi Database Rawat Jalan Rumah Sakit Menggunakan Mysql - Wilsen Grivin Mokodaser; Monica Dwijayanti; Samidi Samidi (Fakultas Ilmu Komputer, Universitas Klabat, 2022)
The need for outpatient hospital services that can be accessed quickly by the community is a very important aspect. By looking at the downturn caused by the Covid-19 pandemic that has hit the world since 2019 and has an impact on various economic aspects including hospital services, digitizing the hospital system must be implemented to be a solution in providing fast services for patients who come for treatment. The information system is not without problems, as the amount of data increases so that the selection of the right database including the use of appropriate queries can help provide accurate and fast output. indexing method can be applied to tables with a large number of databases. the use of subqueries as with previous research shows an increase in data access performance.